Paediatric epilepsy surgery in a middle-income country: the red cross war memorial children's hospital experience - Louw, Lizet (Division of General Surgery, 2023)
Purpose While epilepsy surgery has been shown to reduce seizure frequency and severity and even cures seizures in children with drug-resistant epilepsy, data from middle-income countries (MIC) are lacking. Method This study is a retrospective review of children with drug-resistant epilepsy who underwent surgical treatment at Red Cross War Memorial Children's Hospital (RCWMCH) between 1 January 2000 and 31 December 2021 (HREC: 140/2020). Results During the 21-year study period, 60 patients underwent epilepsy surgery for drugresistant epilepsy. The median age of the children was seven years (IQR 4.81-10.27years) at the time of surgery, with a male predominance of 33 patients. The most common surgical procedure performed was an anterior temporal lobectomy for temporal lobe epilepsy in 19 cases (31.7%), followed by peri-insular hemispherotomy in 9 cases (15.0%) and frontal lobectomy in 8 cases (13.3%). Of the 60 patients, complete records were available for 55 patients noting complications in 11 (20.0%), of which 4 cases (7.3%) had major complications. Notably, 2 patients (3.6%) had new-onset psychiatric symptoms. The long term outcomes after surgery showed 1-year seizure freedom in 32 patients (58.2%); among these, 21 patients (38.2%) could stop ASM one year after surgery, 17 patients (30.9%) had a recurrence of their seizures, and three had to restart ASM after 2-3 years. Eight patients (14.5%) required repeat surgery. The one-year-Modified Engel scoring for the study population was: 1-A in 52.7%, I-B in 3.6%, I-C in 1.8%, II-A in 15.8%, III-A in 10.9%, IV-A in 3.6% and IV-B in 10.9%. The most common histological finding in anterior temporal lobectomy (ATL) was focal cortical dysplasia (FCD), found in 11 patients (57.9%). The periinsular hemispherotomy (PIH) cases had equal numbers of FCD and Rasmussen's encephalitis in 4 patients (44.4%). The number of FCD in this series is much higher than in international data. Conclusion Epilepsy surgery is an effective and attainable intervention for drug-resistant epilepsy in the paediatric population despite limited resources and challenging aetiological profiles. Low complication rates were comparable to international data, with good seizure freedom outcomes.